Nursing Management of Neonatal Hypertension in the Neonatal Intensive Care Unit-An Updated Review - Alsulaiman, Fahad Saud Mohammad; Khawlah Ali Hamad Hakami,; Hind Mkhoot Alfhigi,; Slama Abdallah Aldukhil Allah,; Salha Shahi Alanzi,; Arwa Ghunaim Aldhaferi,; Masiraha Hawaj Noman Aljameeli,; Saimah Hassan Ibrahim Habib,; Sameer Ali Ibrahim Zakri,; Ehdaa Kazim Mohammed Yahya,; Esahaq Yacop Aljubili,; Al-Hanouf Suleiman Al-Numan,; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Neonatal hypertension is increasingly recognized as a clinically significant condition, particularly among premature infants in neonatal intensive care units. Historically, limited normative blood pressure data and variability in measurement methods hindered early diagnosis and management. The condition arises from multifactorial etiologies, including prematurity-related complications, renal pathology, cardiovascular abnormalities, genetic factors, and environmental exposures. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to provide an updated, comprehensive overview of the nursing management of neonatal hypertension, emphasizing diagnostic approaches, etiologic considerations, monitoring techniques, and evidence-based treatment strategies. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative review methodology was employed, synthesizing current literature related to blood pressure measurement techniques, pathophysiology, epidemiology, clinical presentation, diagnostic evaluation, management, prognosis, and interprofessional collaboration in neonatal hypertension. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Accurate diagnosis relies on repeated blood pressure measurements using standardized invasive or noninvasive methods. Prematurity and renal disorders remain the leading causes. Nonrenal factors—such as bronchopulmonary dysplasia, endocrine disorders, and environmental exposures—also contribute. Management centers on addressing underlying causes, optimizing nursing surveillance, and employing pharmacologic or surgical treatments when indicated. Early intervention mitigates risks of end-organ damage, including renal injury, cardiac dysfunction, and neurologic sequelae. Effective care requires interprofessional coordination among neonatologists, nephrologists, nurses, pharmacists, and caregivers. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Neonatal hypertension is a complex, multifactorial condition requiring vigilant nursing assessment, accurate monitoring, and individualized treatment. Early recognition, thorough evaluation, and targeted management substantially improve outcomes, while structured interprofessional collaboration enhances continuity of care and long-term health.